An Empirical Approach to Investigate the Possibility Of Consumer Driven Sustainability Transformation Of Indian Textile And Apparel Industries (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Consumers are bestowed with more power than they think. With the rising income level and the consumer base for fast fashions, the per capita consumption has increased significantly in India. Production of cotton, the primary raw material of the cotton textile and apparel industry is very resource intensive, wasteful and polluting. The production and consumption of cotton have very high environmental footprint. Several studies have pointed out the importance of sustainable production and consumption in reducing the environmental footprint of the textile industry. The paper aims in analysing the perception of ‘Sustainability’ of textile products as a purchasing decision making criteria for the end user consumers in India. The study focusses on the end user consumption side as they are a potential driver for sustainability transition in India. The study is based on three axioms that perception generates demand, demand motivates process transformation, and process transformation enables enterprises to navigate through the market challenges. The paper also identifies the challenges and mitigating strategies in the landscape level process transformation required for increasing the environmental sustainability performance of the products.